A Commentary on Two Scientific Studies of the ruma (רומא) Jar from Qumran - Yellin, Joseph (Dead Sea discoveries, 2015)
Two chemical studies of the ruma jar from Qumran Cave 7 are examined. It is shown that these researches, seemingly at odds, have more in common than not. It is argued that the evidence from both studies point to Jerusalem as the origin of the ruma jar although one of the studies concludes that the ruma jar was locally made in Qumran from local clay. The data from both studies are consistent but the interpretations differ.